Decolonizing Deliberative Democracy: Perspectives from Below - Banerjee, Subhabrata Bobby (Journal of business ethics, 2022)
In this paper I provide a decolonial critique of received knowledge about deliberative democracy. Legacies of colonialism have generally been overlooked in theories of democracy. These omissions challenge several key assumptions of deliberative democracy. I argue that deliberative democracy does not travel well outside Western sites and its key assumptions begin to unravel in the ‘developing’ regions of the world. The context for a decolonial critique of deliberative democracy is the ongoing violent conflicts over resource extraction in the former colonies of Africa, Asia and Latin America. I argue that deliberative democracy cannot take into account the needs of marginalized stakeholders who are defending their lands and livelihoods. The paper contributes to the literature by (1) offering a critique of hegemonic models of democracy that cannot address issues of inequality and colonial difference and (2) offering possibilities to imagine counterhegemonic alternatives for a democratization of democracy from below.